2016 Global Food Policy Report: The future of a sustainable global food system - Voegele, Juergen (2016)
Presentation by Juergen voegele, Senior Director for the Agricultural Global Practice at the World Bank, for the launch of the 2016 Global Food Policy Report on March 31, 2016 in Washington, DC